The Influence of Marketing Communication and Social Media Marketing on Increasing Brand Awareness to Create an Intention to Buy at University X in Surabaya - Vincentius Yasashi Alvin Santoso (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to examine the effect of marketing communication and social media marketing on increasing brand awareness to increase intention to buy at an University. This study uses quantitative methods using SmartPLS for data processing. The number of respondents in this study were 155 people who were selected by purposive sampling method. The requirements are prospective students who have registered and know marketing communication information at university X. The results show that in marketing communication, events and publicity do not have a significant effect on brand awareness while advertising, sales promotion, personal selling and direct marketing have a significant effect on brand awareness. Meanwhile, brand awareness has a significant effect on intention to buy.